The Determinants of Corporate Social Responsibility Disclosure: Evidence from Energy Sector Firms - Leny Suzan; Annaya Rizha Fairy (Yayasan Riset dan Pengembangan Intelektual, 2023)
Corporate social responsibility expects firms to work morally and to be worried about the ecological and social ramifications of their exercises. This study aims to investigate how media exposure, slack resources, and profitability affect disclosure of CSR. All organizations in the energy area that were recorded on the Indonesia Stock Trade (IDX) somewhere in the range of 2017 and 2021 make up the number of populations in this review. During a five-year period, 95 samples representing 19 businesses were collected using purposive sampling from the entire population. The quantitative panel data regression analysis used in this study will be calculated with the help of the statistical software EViews 12. The discoveries uncover that profitability, slack resources, and media exposure all affect CSRD. Media exposure has a partial positive impact, but profitability and slack resources have no effect on disclosure of CSR.